Is a high-risk clinical target volume required? Evaluation of the dosimetric feasibility based on T staging - Yuan, Xingxing; Yan, Chao; Peng, Shiyi; Chen, Zhiping; Lu, Tianzhu; Gong, Qiaoying; Qiu, Yang; Xiong, Wenming; Ao, Fenghua; Li, Guoqing; Li, Jingao; Tu, Ziwei (Frontiers in Oncology, 2022)
Abstract Background: Clinical target delineation is a primary focus in the field of radiotherapy. This study aimed to investigate whether high-risk clinical target volume can be removed in nasopharyngeal carcinoma patients with different T stages. Materials and Methods: We designed a test plan without the high-risk clinical target volume for 111 nasopharyngeal carcinoma patients and further compared the test plans with the treatment plans in the parameters of planning target volumes and the radiation dose to normal organs. Results: Our data showed that when high-risk clinical target volume was abnegated, target coverage, conformity indices, and homogeneity indices of planning target volumes and doses of normal organs were not influenced in the T4 nasopharyngeal carcinoma patients, and more than 95% of the high-risk planning target volume area could still be covered by the 60 Gy dose line. However, only some T1–3 patients achieved the ideal dose coverage, and even fewer after induction chemotherapy (62.8% vs. 41.2%, p = 0.018). Gross tumor volume was positively correlated with the target coverage of the original high-risk planning target volume in the test-plan (p = 0.0001). Gross tumor volume can be used to predict whether the target coverage of high-risk planning target volume is more than 95% (area under the curve = 0.868). Conclusion: Omitting high risk clinical target volume can be considered in patients with T4 nasopharyngeal carcinoma according to physical evaluations. However, this approach is only suitable for a specific subset of T1–3 patients.